Collaboration between academics and librarians: A literature review and framework for analysis. Issue 1 (2nd May 2014) - Pham, Hue Thi; Tanner, Kerry
Abstract : Purpose: – The purpose of this paper is to examine recent literature for a review of the concepts of collaboration in library and information science and related disciplines and to develop a conceptual framework for application in academic contexts globally. Design/methodology/approach: – An investigation of literature exploring the multifaceted meanings and dimensions of collaboration and subsequent development of a framework for analysis. To exemplify the use of the framework in analysing collaboration between academics and librarians, and to demonstrate the impact of context on collaboration, the paper explores the situation and educational contexts in two national settings – one a developed country (Australia) and the other a developing country (Vietnam). Findings: – Contextual factors have a substantial impact on the nature of collaboration between academics and librarians. The collaboration framework developed is applied to academic settings in two countries, Vietnam and Australia, and dimensions of collaboration are compared and contrasted in the two countries. Insights and implications are drawn concerning the distinctive features of effective collaboration as well as the achievements and challenges of such collaborative partnerships. Research limitations/implications: – This literature-based article reports on the first part of a larger research project. Further development and application of the conceptual framework in studying the collaborative relationship between academics and librarians empirically are deemed important. Originality/value: – This paper provides insights into the current condition and challenges in developing collaboration between academics and librarians. The proposed framework is beneficial to academics, librarians and universities interested in addressing the issues of this partnership in various academic contexts.